Banking sector crises and inequality - Honohan, Patrick, 1949- 1949- (Policy research working paper, 2005)
"An apparent temporary narrowing of income inequality has been observed during several recent banking crises. But it would be a mistake to conclude that such crises don't matter for the poor. For one thing, the correlation is not strong, and the opposite pattern has also been present. Besides, the poor are much less able to absorb a cut in income: safety-net policies are crucial during a downturn even if the gap between rich and poor has temporarily narrowed. More fundamentally, distributional shifts during the crisis may be less important than the fact that underlying financial policy and infrastructures conducive to crisis can also be associated with more unequal societies."--World Bank web site